COVID vaccination and asthma exacerbation: might there be a link?. (November 2021) - Colaneri, Marta; De Filippo, Maria; Licari, Amelia; Marseglia, Alessia; Maiocchi, Laura; Ricciardi, Alessandra; Corsico, Angelo; Marseglia, Gianluigi; Mondelli, Mario Umberto; Bruno, Raffaele
Highlights: Worldwide, the prevalence of asthma is high among teenagers and school children. Monitoring adverse events following coronavirus disease 2019 (COVID-19) vaccination is important for practitioners. There are plans for mass COVID-19 vaccination of teenagers and school children. The effect of COVID-19 vaccination on asthmatic individuals is unknown and unreported. This article reports the first case of asthma exacerbation following COVID-19 vaccination. ABSTRACT: Introduction: There is ongoing debate regarding the role of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection in asthma exacerbation, and its long-term impact on the lung function of individuals with asthma. In contrast, the potential impact of coronavirus disease 2019 (COVID-19) vaccination on asthma is entirely unexplored. Case study: This study examined a challenging case of severe asthma exacerbation in a 28-year-old female following two doses of the mRNA-based vaccine BNT162b2 (Pfizer-BioNTech) at IRCCS Policlinico San Matteo in Pavia, Italy. The patient, a fourth-year resident at the hospital, was vaccinated in early 2021. She was an occasional smoker with a 10-year history of asthma and seasonal allergic rhinitis. She tested negative for SARS-CoV-2 on several molecular swabs and serology tests. Results: After receiving the second dose of vaccine, the patient started to experience worsening of respiratory symptoms. Following several episodes and a severe asthma attack, the patient required treatment with mepolizumab, a biologic drug (interleukin-5) antagonist monoclonal antibody. Conclusion: This single case study is insufficient to draw conclusions about the association between asthma exacerbation and the COVID-19 vaccine. While the cause–effect link between vaccination against SARS-CoV-2 and worsening of asthmatic disease might only be suggested at present, this case is a valuable prompt for further investigation. This is particularly true from the perspective of mass vaccination of adolescents and children currently underway across the globe.